Promotion in Mexico of the hermetic metal silo to minimize stored grain losses - Odjo, Sylvanus; González Regalado, Jessica; Ruíz Albarrán, Victor Hugo; Loon, Jelle J. van; Verhulst, Nele (International Maize and Wheat Improvement Center, 2023)
This publication reports on the experience of CIMMYT promoting hermetically sealed metal silos to minimize losses in stored maize and other grains under smallholder farming conditions in Mexico. The metal silo was developed through the "Postcosecha" project first implemented in the 1980s in Central America and introduced in Mexico in the 1990s. The hermetic metal silo promoted in Mexico has evolved into a more advanced version with a conical upper shape and the use of bronze or aluminum plugs to increase airtightness and eliminate the need to use poisonous aluminum phosphide tablets. Through CIMMYT and Mexican partnerships, the manufacturing process for the silos has been established in a Mexican Norm to standardize the dimensions. CIMMYT and its network of collaborators have been promoting the hermetic metal silo through the hub model. Farmers typically store maize grain in woven polypropylene bags with or without chemical insecticides; grain damage can reach 32%, in tropical conditions after three months of storage. In side-by-side comparisons of the hermetic metal silo and farmers' practices, the hermetic metal silo kept losses to less than 3%. Local artisans were trained in manufacturing the silos and to facilitate access of smallholder farmers to the technology, but the lack of awareness, business models, and credits have hindered the widespread adoption of hermetic metal silos. Promotion of the hermetic metal silo, including stakeholder collaboration leading to institutional anchoring, should continue, to reduce storage losses and to safeguard farm households' food security, health, and profits.